Potential littoral sediment transport along the coast of south eastern coast of india (2010)
In the nearshore zone of present study area, the movement of sand alongshore is due to the action of waves and currents. The sediment movement along the shoreline of study area is mainly governed by the forces associated with the incoming waves and the availability of sediments within the area. Thepresent investigation has beenmadeas an attempt to appreciate the sediment movement in relation to wave activity along the coast. The longshore sediment transport is higher in the northerly direction as compared to southerly direction. The normal condition is for and to be moved annually or more frequently in the shallows and on the beach. Waves and wave-driven currents cause longshore drift of sand along the beach and offshore. The net erosive nature of the study area (except Kanyakumari) from March to October is due to the prevalence of high waves from S and SE directions.